Pembuatan Diagram Alir Standard Operating Procedure Penerimaan Kas BLUD Air Minum Kota Cimahi - Bahiyyah, Khariidatul (PT. Banjarese Pacific Indonesia, 2024)
The purpose of community service which raised the title of Assistance in Making Standard Operating Procedure Flow Diagrams for Cimahi City Drinking Water BLUD Cash Receipts to improve the financial performance of Cimahi City Drinking Water BLUD, one of the things that is of concern is that there are differences in data between the Revenue Treasurer and the Accounting Department. While the accounting department is duty to provide financial statement data to DPKP Cimahi City which will then be consolidated to BPKAD Cimahi City. When the accounting department reconciles data with BPKAD, there is different income data between BAPPENDA and BPKAD. This happened because there was no data reconciliation first between the revenue treasurer and the Accounting Section of the Cimahi City Drinking Water BLUD before the data was provided to interested parties. So far, BLUD Drinking Water uses SOPs that have not been updated. The problem occurred because the Cash Receipt SOP had not been updated and had not complied with the SOP preparation standards set by the local government. Needed to create a new Cash Receipt SOP so that the data provided by the Revenue Treasurer or Accounting Section becomes one vote. The methods used in preparing SOP are interviews, observations, and literature studies. The result of the community service carried out is that there is an excel format of the latest Cash Receipt SOP even though it has not been ratified because it is still waiting for the completion of SOP in other divisions.